Exploring the Efficacy of Plant Extracts for Sustainable Whitefly (Bemisia tabaci) Management in Agricultural Systems - Dr. Jamal Khan; Prof. Saba Mahmood; Dr. Shahid Abbas (Indus Journal of Social Sciences, 2023)
This research delves into the multifaceted exploration of plant extracts for sustainable whitefly (Bemisia tabaci) management in agricultural systems. Employing an array of natural extracts—water, neem extract, tobacco extract, compost extract, eucalyptus extract, and ginger extract—this study systematically evaluates their efficacy as potential alternatives to conventional chemical control measures. The experimental design encompasses a randomized complete block layout to ensure robust comparisons and statistical validity. Each plant extract is meticulously applied to designated plots within an agricultural setting, and whitefly populations are monitored over specified intervals. The efficacy of treatments is assessed through visual observations, quantitative measurements, and statistical analyses. Furthermore, the ecological impact of these plant extracts on non-target organisms, including beneficial insects, is examined to ascertain their environmental compatibility. Preliminary findings suggest varying degrees of efficacy among the plant extracts, with neem extract and tobacco extract demonstrating notable whitefly suppression. Compost extract and eucalyptus extract exhibit moderate effectiveness, while water and ginger extract serve as experimental controls. This study contributes valuable insights into the potential of plant extracts as sustainable tools for whitefly management, offering environmentally friendly alternatives for integrated pest management strategies in agriculture.